Pre-pregnancy levels of peripheral natural killer cells as markers for immunomodulatory treatment in patients with recurrent miscarriage - Kuon, Ruben-Jeremias; Hudalla, Hannes; Rösner, Sabine; Strowitzki, Thomas; Daniel, Volker; Toth, Bettina (Archivum immunologiae et therapiae experimentalis, 2017)
Immunological risk factors in patients with recurrent miscarriage (RM) are discussed controversially. Abnormalities of natural killer cells (NK) have been described in RM patients. Lipid infusions are known to modulate lymphocyte subsets. The aim of this study was to identify immune parameters that predict success of treatment with lipid infusions in RM patients with elevated NK. In sum, n = 341 couples with RM were screened for established risk factors and peripheral lymphocyte subpopulations as well as uterine NK cells. We identified n = 136 patients with ≥ 2 consecutive RM and elevated NK. So far, n = 40 RM patients with NK disorders were treated with lipid infusions starting at positive pregnancy test, every 2 weeks until 12 + 0 weeks of gestation (GW) or miscarriage. The pre-pregnancy immune diagnostics in idiopathic RM (iRM) patients with ongoing pregnancy were compared to the group with miscarriages and healthy controls (n = 15). Pre-pregnancy immune diagnostics differed significantly between the groups, with significant higher levels of peripheral NK (% and /µL) in iRM patients who miscarried again compared to controls (p = 0.0035 and p = 0.0019). Furthermore, iRM patients show lower percentages of CD3+ lymphocytes than healthy controls (p = 0.0049). In n = 22/40 (55%) patients, pregnancy is ongoing >12 + 0 GW. RM patients with very high pre-pregnancy peripheral NK (pNK) lymphocytes might not benefit from lipid infusions. Pre-pregnancy immunomodulatory treatment in RM patients might be helpful to lower pNK levels and establish an immune environment which is supportive for fetal development.